MECHANICAL PROPERTIES OF BANANA FIBRE REINFORCED POLYSTER COMPOSITES - S V, Anil kumar; Bawge, Ganapathy; Chandra Shekara V C; Mohammad Rafi H Kerur; Somashekar H M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the present scenario, there has been a rapid attention in research and development in the natural fibre composite field due to its better formability, abundant, renewable, cost-effective and eco-friendly features. This work makes use of easily available banana fibres as a reinforcement material for the polyester matrix to produce the effective composite material. The Banana fibre reinforced polyester composite material is prepared by adopting Hand Lay-up method subjected to a Tensile and Impact tests and the results are analysed. The tensile strength of the single layer banana fibre composite is greater than the double layer banana fibre composite, it is because of the improper load distribution in the double layer banana fibre composite material. Since the tensile strength depends on the interfacial bonding between the matrix and fibres, the interfacial bonding in the double layered composite is lesser when compared to that of the single layered composite material. The impact strength of single layer banana fibre composite is lesser than the double layer banana fibre composite because as the fibre content increases the energy absorbing capacity of the material also increases. The impact strength of the banana fibres is found to be comparable and better than that of the glass fibres, so banana fibres can replace glass fibres in terms of its impact strength.